Monetary policy and the cross-section of stock returns: a FAVAR approach - Pires, Victor Duarte Garcia (2012)
We use a factor-augmented vector autoregression (FAVAR) to estimate the impact of monetary policy shocks on the cross-section of stock returns. Our FAVAR combines unobserved factors extracted from a large set of nancial and macroeconomic indicators with the Federal Funds rate. We nd that monetary policy shocks have heterogeneous e ects on the crosssection of stock returns. These e ects are very well explained by the degree of external nance dependence, as well as by other sectoral characteristics.